2022
DOI: 10.1101/2022.07.12.496461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analysis of chromatin and expression reveals age- and sex-associated alterations in the human heart

Abstract: Sex differences and age-related changes in the human heart at the tissue, cell, and molecular level have been well-documented and many may be relevant for cardiovascular disease. However, how molecular programs within individual cell types vary across individuals by age and sex remains poorly characterized. To better understand this variation, we performed single-nucleus combinatorial indexing (sci) ATAC- and RNA-Seq in human heart samples from nine donors. We identify hundreds of differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…The required fields represent attributes that are often variable within or across studies and are often identified as strong covariates correlated with gene expression variation within cells. 21,22 Similar to previous experimental data coordination efforts, established ontologies and other community resources are used for standardization wherever possible for consistency and to improve the filtering capabilities of datasets (table S2). 23,24,25 To fully capture gene count information for each dataset, a layer of raw data, meaning nonnormalized, is required for submission of data from all transcriptomic assays to fulfill common computational reuse cases.…”
Section: Raw Countsmentioning
confidence: 99%
“…The required fields represent attributes that are often variable within or across studies and are often identified as strong covariates correlated with gene expression variation within cells. 21,22 Similar to previous experimental data coordination efforts, established ontologies and other community resources are used for standardization wherever possible for consistency and to improve the filtering capabilities of datasets (table S2). 23,24,25 To fully capture gene count information for each dataset, a layer of raw data, meaning nonnormalized, is required for submission of data from all transcriptomic assays to fulfill common computational reuse cases.…”
Section: Raw Countsmentioning
confidence: 99%
“…We hope that eSVD-DE would be beneficial for inspiring cohort-wide DE tests for future single-cell assays beyond scRNA-seq and single-cell eQTL analyses where abundant individual-level covariate effects must be adequately removed. Additionally, we are curious about broader settings where instead of having case and control individuals within a cohort, we are interested in testing if continuous covariates such as age have a substantial transcriptomic impact on specific cell types, as discussed in [53].…”
Section: Discussionmentioning
confidence: 99%
“…We hope that eSVD-DE would be beneficial for inspiring cohort-wide DE tests for future single-cell assays beyond scRNA-seq and single-cell eQTL analyses where abundant individual-level covariate effects must be adequately removed. Additionally, we are curious about broader settings where instead of having case and control individuals within a cohort, we are interested in testing if continuous covariates such as age have a substantial transcriptomic impact on specific cell types, as discussed in [51].…”
Section: Discussionmentioning
confidence: 99%